(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Patients with breast cancer may develop recurrence even after adequate primary therapy. Besides clinical examination and imaging, serum protein tumor markers (SPTMs) measurements are used for follow-up. To find out the association of two postoperative SPTMs (e.g., Carcinoembryonic antigen/CEA, Carbohydrate antigen15-3/CA15-3) with the future recurrence of breast cancer among Bangladeshi women. Prospective-observational study was conducted among purposively-selected one hundred Patients (who underwent surgery before six months) during their routine follow-up visit to an oncology/surgical setting in Dhaka Medical College Hospital, Bangladesh. Postoperative CEA (cut-off:5ng/mL) and CA15-3 (30 U/mL) were measured at a single point time by ‘chemiluminescent Immuno assay.’ Patients were then followed up for one year to detect any recurrence. Quantitative and categorical variables were compared by Student’s t-test and Fisher’s exact test, respectively. Sensitivity, specificity, and AUC (Area under the curve) of both SPTMs were estimated. Most (64%) of the patients were postmenopausal (Mean-age: 49.8±12.1) with elevated CA15-3 (32%) and CEA (18%). Overall recurrence was 18%, and only CA15-3 was found to be associated with visceral (hepatic and bone) recurrence (P=0.015). The sensitivity and specificity of CEA and CA15-3 were 22.22%, 82.9%, and 66.7%, 75.6%, respectively, while combined sensitivity increased by 6.25%. The AUC of the receiver operating characteristics (ROC) curves were 0.62, 0.82, and 0.88 for CEA, CA15-3, and combination, respectively. Postoperative CA15-3 has been shown to have the capacity to rule out visceral recurrence with a reasonably high probability. Since the specificity of CA15-3 is pretty good, it may detect early recurrence following primary treatment of carcinoma breast.